Pengaruh Implementasi Model Pembelajaran Quantum Learning Dalam MAPEL PAI Terhadap Keberhasilan Siswa Di Kelas VIII SMPN 2 Cikajang - Raito, Raito; Nizar, Ahmad (STAI Al-Musaddadiyah Garut, 2022)
Student learning outcomes remain a perennial issue in the field of education. At SMPN 2 Cikajang, there was a noted decline in the final semester exam scores for Islamic Religious Education (PAI) in the eighth grade during the 2021-2022 academic year. Quantum Learning, a pedagogical model that fosters active student engagement and creates an inclusive and comfortable learning environment, has been proposed as a solution to address this decline. The objectives of this study are to: (1) describe the implementation of the Quantum Learning model in PAI lessons; (2) assess the learning achievements of eighth-grade students in PAI at SMPN 2 Cikajang; and (3) analyze the impact of the Quantum Learning model on the students' PAI learning outcomes. This research employs an inferential quantitative method, collecting data and information about the phenomenon under study. Data collection techniques include questionnaires distributed to 27 respondents and observations. The results indicate that the Quantum Learning model in PAI is highly effective, with an average score of 4.19, placing it in the 3.01-4.00 interval, which falls under the